Effect of biotechnologically modified alginates on LDH structures. Issue 3 (1st September 2015) - Sieber, Volker; Plank, Johann; Sperl, Nadine; Schmid, Jochen; de Reese, Johanna
Abstract : Four alginates possessing different guluronic/mannuronic acid ratios and one acetylated alginate were investigated with respect to their behaviour during intercalation into layered double hydroxides (LDHs). Two alginates were commercial products while the others were synthesised by way of bacterial fermentation and in one sample followed by enzymatic treatment. Intercalation was performed by way of co-precipitation of aluminium nitrate and zinc nitrate in alginate solution at a pH of 8·5–9. The products were characterised by powder X-ray diffraction, elemental analysis, wide-angle X-ray scattering, scanning electron microscopy and magic angle spinning (MAS) NMR spectroscopy. All alginates intercalate well into the Zn2 Al-LDH host structure. With an increase in the content of guluronic acid in the alginate, the d -spacing (interlayer distance) in the alginate-LDH compound increases from 1·28 to 1·85 nm. Similarly, acetylation of the carboxylic groups leads to an increased steric volume of such alginate and therefore to a higher d -spacing (1·72 nm). The results indicate that different guluronic/mannuronic acid ratios can be used to trigger the steric size of the alginates and consequently the d -spacing of the alginate-LDHs. 13 C CP MAS NMR spectroscopy confirmed an interaction between the carboxylic groups present in the alginate with the inorganic main layer.